OPEN CODE PROGRAM FOR THE BIDIMENSIONAL ANALYSIS OF SLOPES' STABILITY BY THE EQUILIBRIUM METHOD - Exneyder Andrés Montoya-Araque; Ludger O. Suarez-Borgoa (Revista de la Facultad de Ciencias, 2016)
This article makes a recopilation about the past developments in computer programming in regard to the analysis of slope stability applied to geotechnics. After that, the article presents the computer program developed by the authors which allows to solve slope stability problems under the method of limit equilibrium with the solutions propossed by Fellenius and Bishop using PYTHON3. The program consist of 22 procedural independent functions, which as a set form a nested system which allow to run the complete analysis; all of these helped by a graphical user interfase run from the terminal. Results are presented graphically. Finally, this article presents some examples and validations. We can conclude that the program is in principle for academic uses because it does not solve the genral solution; but because it is an open source code it can be used for future implementations inclusive the general ones.